Acoustic Measures of Dysphonia in Amyotrophic Lateral Sclerosis. - Maffei, Marc F.; Green, Jordan R.; Murton, Olivia; Yunusova, Yana; Rowe, Hannah P.; Wehbe, Farah; Diana, Kathleen; Nicholson, Katharine; Berry, James D.; Connaghan, Kathryn P. (Journal of Speech, Language & Hearing Research, 2023)
Purpose: Identifying efficacious measures to characterize dysphonia in complex neurodegenerative diseases is key to optimal assessment and intervention. This study evaluates the validity and sensitivity of acoustic features of phonatory disruption in amyotrophic lateral sclerosis (ALS). Method: Forty-nine individuals with ALS (40-79 years old) were audio-recorded while producing a sustained vowel and continuous speech. Perturbation/noisebased (jitter, shimmer, and harmonics-to-noise ratio) and cepstral/spectral (cepstral peak prominence, low-high spectral ratio, and related features) acoustic measures were extracted. The criterion validity of each measure was assessed using correlations with perceptual voice ratings provided by three speech-language pathologists. Diagnostic accuracy of the acoustic features was evaluated using area-under-the-curve analysis. Results: Perturbation/noise-based and cepstral/spectral features extracted from/a/were significantly correlated with listener ratings of roughness, breathiness, strain, and overall dysphonia. Fewer and smaller correlations between cepstral/spectral measures and perceptual ratings were observed for the continuous speech task, although post hoc analyses revealed stronger correlations in speakers with less perceptually impaired speech. Area-under-the-curve analyses revealed that multiple acoustic features, particularly from the sustained vowel task, adequately differentiated between individuals with ALS with and without perceptually dysphonic voices. Conclusions: Our findings support using both perturbation/noise-based and cepstral/spectral measures of sustained/a/to assess phonatory quality in ALS. Results from the continuous speech task suggest that multisubsystem involvement impacts cepstral/spectral analyses in complex motor speech disorders such as ALS. Further investigation of the validity and sensitivity of cepstral/spectral measures during continuous speech in ALS is warranted.